2007
DOI: 10.1021/je060290k
|View full text |Cite
|
Sign up to set email alerts
|

Stability Constants of Chloride Complexes of Lanthanum

Abstract: The stability constants of chloro complexes of La 3+ were determined in perchloric acid media by means of a solvent extraction method. Dinonyl napthalene sulfonic acid was used as one extractant, and the lanthanum concentration was measured by an UV-VIS method using xylenol orange at pH 6. The values obtained for β La,Cl I are (1 ( 0.2, 0.76 ( 0.09, and, 0.67 ( 0.15) mol -1 ‚dm 3 for (2, 3, and 4) mol‚dm -3 , respectively. For β La,2Cl they are (0.2 ( 0.1, 0.09 ( 0.02, and 0.1 ( 0.03) mol -2 ‚dm 6 for (2, 3 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 17 publications
(46 reference statements)
0
19
1
Order By: Relevance
“…From the coordination number histogram of Cl – anions hydrating the La 3+ cations and, consequently, knowing the concentrations of the various species in the solution, it is possible to estimate the stability constants for the various ion complexes. For example, for the equilibrium between a solvated anion and solvated cation with the corresponding ion-paired complex, we can write L a ( a q ) 3 + + C l ( a q ) L a C l ( a q ) 2 + and calculate β L a , C l = [ L a C l 2 + ] [ L a 3 + ] [ C l ] Using the percentages shown in the lower panel of Figure , we obtain a value of ≈1.4 ± 0.1 mol –1 dm –3 which is a reasonable estimate when compared to the range of values found in the literature (0.67–1.6 mol –1 dm –3 ) for lanthanum chloride solutions of ionic strengths in the range from 1 to 4 mol dm –3 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the coordination number histogram of Cl – anions hydrating the La 3+ cations and, consequently, knowing the concentrations of the various species in the solution, it is possible to estimate the stability constants for the various ion complexes. For example, for the equilibrium between a solvated anion and solvated cation with the corresponding ion-paired complex, we can write L a ( a q ) 3 + + C l ( a q ) L a C l ( a q ) 2 + and calculate β L a , C l = [ L a C l 2 + ] [ L a 3 + ] [ C l ] Using the percentages shown in the lower panel of Figure , we obtain a value of ≈1.4 ± 0.1 mol –1 dm –3 which is a reasonable estimate when compared to the range of values found in the literature (0.67–1.6 mol –1 dm –3 ) for lanthanum chloride solutions of ionic strengths in the range from 1 to 4 mol dm –3 …”
Section: Resultsmentioning
confidence: 99%
“…Using the percentages shown in the lower panel of Figure 5, we obtain a value of ≈1.4 ( 0.1 mol À1 dm À3 which is a reasonable estimate when compared to the range of values found in the literature (0.67À1.6 mol À1 dm À3 ) for lanthanum chloride solutions of ionic strengths in the range from 1 to 4 mol dm À3 . 30 To complete the picture of the ion interactions in the 1 m LaCl 3 solution, Figure 6 shows the ClÀO water and ClÀH water pair distribution functions and running coordination numbers. As expected for the chloride ions, the average hydration number for these ions is approximately six, although a little less since a significant number of these anions are, as previously seen, directly ion paired with the La 3þ cations.…”
Section: ' Results and Discussionmentioning
confidence: 99%
“…From equilibrium constants measured using different techniques and under different conditions (ionic strengths between 1 and 4 M, β La,Cl = 0.67 to 1.6 mol dm –3 ), , free energies between Δ G = −0.3 to +0.2 kcal/mol can been derived for this reaction. Extrapolation to zero ionic strength has afforded an estimate of log β 0 La,Cl = 1.43 (±0.12) mol dm –3 , corresponding to Δ G 0 = 2.0 kcal/mol. Despite the shortcomings of our DFT level discussed above, the CPMD-derived Δ A in eq is in excellent agreement with this value, apparently benefiting from fortuitous error cancellation.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study employed solvent extraction methods to determine stability constants in Er chloride solutions with ionic strengths varying from infinite dilution through 4 mol/dm 3 . Equilibria were established in aqueous solution, and then the free, uncomplexed Er was extracted into n -heptane using dinonylnapthalene sulfonic acid following an earlier discussed procedure . These extractions were carried out as a function of chloride concentration in the aqueous phase, and after extraction into the organic phase the Er concentration was quantified with visible spectrophotometry.…”
Section: Discussionmentioning
confidence: 99%
“…Equilibria were established in aqueous solution, and then the free, uncomplexed Er was extracted into n-heptane using dinonylnapthalene sulfonic acid 21 following an earlier discussed procedure. 34 These extractions were carried out as a function of chloride concentration in the aqueous phase, and after extraction into the organic phase the Er concentration was quantified with visible spectrophotometry. For solutions with ionic strengths g1 the authors compared fits to their extraction results using linear and second-order polynomial fitting, from which they concluded that the errors in the latter were generally slightly higher.…”
Section: Discussionmentioning
confidence: 99%